Changes in antibiotic sensitivity in strains of Staphylococcus aureus, 1952-78. - Hassam, Z A (1978)
Two hundred strains of Staphylococcus aureus isolated from outpatients with infections of the skin and subcutaneous tissues were tested for sensitivity to penicillin, erythromycin, tetracycline, sodium fusidate, methicillin, clindamycin, chloramphenicol, and gentamicin. One hundred and sixty-three (81.5%) of the strains were resistant to penicillin and 16 (8%) resistant to tetracycline. Incidence of resistance to other antibiotics was low. No strain was resistant to chloramphenicol, gentamicin, or methicillin. When compared with results of earlier studies, there was an increase in the incidence of resistance to penicillin and tetracycline, but no appreciable increase in resistance to other antibiotics.